Jiro Dreams of Sushi: A Circuit of Shokunin - Anton Sutandio (Lingua Cultura, 2023)
The research looked at David Gelb’s 2011 documentary, Jiro Dreams of Sushi, from the shokunin concept’s perspective. Referring to Hall’s circuit of culture, the research focused on two interrelated links within cultural studies: production and consumption. Production and consumption referred to the sushi culture. Shokunin was defined as mastery of one’s profession or artisans. The film reflected this concept through the character, Jiro Ono, who dedicated his life to excelling in making sushi. The method applied in the research was qualitative. The data were drawn from the film’s cinematography which referred to the camerawork, and mise-en-scène, which referred to everything on the film frame, as part of the film studies method applied. The findings show that in terms of production and consumption of sushi within the circuit of culture, the film has shown the interrelated meaning of sushi culture: that in the context of Jiro Ono’s sushi, sushi becomes more than just food, but through its complex production and consumption process, sushi culture becomes a representation of ancient Japanese concept, shokunin, which emphasizes on discipline, perfection, beauty and of course, hard work, and sacrifice. These findings are supported by visualizing the production and consumption through the film’s cinematography and mise-en-scène.